Efecto del porcentaje de diatomeas en la curva compresibilidad del suelo (2019)
This paper presents the results of the consolidation of a diatomatic soil with different percentages of diatoms. The objective was to find considerable differences in four reconstituted soils with 0, 25, 50, and 75% of diatoms, through tests such as Atterberg limits, specific gravity and consolidation using the automated oedometric Consolidaometers of the Julio Garavito Colombian School of Engineering . In addition to these tests, four flights are carried out in the centrifuge at 200 graves at a slope of 45 degrees modeled on the consolidation boxes of the four floors. The results indicated in the liquid limits and in the gravity specify some variations as the percentage of diatoms increases, on the other hand, with respect to the compressibility characteristics of the soil, the compressibility index did not have considerable changes and the flights in the centrifuge not determined a defined fault plane